Comparative image analysis of conventional and thin‐layer preparations in endometrial cytology. Issue 6 (16th July 2012) - Hattori, Manabu; Kobayashi, Tadao K.; Nishimura, Yukari; Machida, Daisuke; Toyonaga, Masumi; Tsunoda, Shinpei; Ohbu, Makoto
Abstract We evaluated the differences in cytologic findings between conventional and thin‐layer preparations in endometrial cytology to introduce the thin‐layer method into routine cytology. Eighty patients who had undergone endometrial cytology and biopsy on the same day were selected and we compared the cytological findings between conventional‐ and thin‐layer preparations (TLP) in endometrial cytology. The numbers of neutrophils and cell clusters in the thin‐layer method were lower than those in the conventional smear (CSS) method. The average number of neutrophils in endometrioid adenocarcinoma was significantly higher than that in normal morphology endometrium and endometrial hyperplasia. Regarding the shape of the cell clusters, ball‐like patterns and round‐edged cell clusters were not identified in CSS. The average number of clusters in CSS was significantly greater than that using the TLP. The average of the nuclear area in CSS was significantly larger than that using the TLP, indicating that the nuclear areas in CSS were more uneven than that using the TLP. In the future, it is expected that liquid‐based cytology will be applied to the cytological diagnosis of a variety of lesions. The influence on cells due to fixation is considerable in liquid‐based preparations. Therefore, if we strive to pick up the differences between CSS and TLP of endometrial samples, the diagnostic accuracy of the latter could be improved. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.